Implementasi Konsep Keadilan dalam Akad Mudharabah: Studi pada Lembaga Keuangan Mikro Syariah - Zulkarnaen, Zulkarnaen; Hakim Siregar, Lukmanul; Muda, Iskandar; Soemitra, Andri; Yusrizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the implementation of the principle of justice (al-‘adl) in mudharabah contracts within Islamic Microfinance Institutions (LKMS) in Indonesia. The rapid growth of the Islamic economy demands the application of contracts that align with Islamic values, one of which is mudharabah—a partnership between the shahibul maal (capital provider) and the mudharib (entrepreneur)—based on fair and transparent profit-sharing principles. The research employs a qualitative method using a library research approach and a comparative analysis between the concepts of fiqh muamalah and modern regulations such as the DSN-MUI fatwas and OJK regulations concerning LKMS. The findings reveal that, conceptually, the mudharabah contract reflects the value of justice through the balance of rights and obligations between capital owners and business managers. However, in practice, LKMS still face several challenges, including institutional dominance in determining profit-sharing ratios (nisbah), low transparency in business reporting, and weak sharia supervision. These issues indicate a gap between the normative principles of fiqh muamalah and their regulatory implementation in practice. This study recommends the formulation of maqashid sharia-based contract frameworks, the enhancement of human resource capacity in fiqh muamalah and Islamic accounting, and the strengthening of the Sharia Supervisory Board’s function to ensure comprehensive implementation of justice in every contract.